2021
DOI: 10.1590/1806-9282.67.suppl1.20200814
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes in the COVID-19 pandemic era

Abstract: OBJECTIVE:To analyze the association between patients with diabetes mellitus and the increased severity and its complications that arise with a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection.METHODS: This is a complementary review of literature in which 14 articles published in 2020 were selected. These reviewed articles were written in both Portuguese and English available in the SciELO and PubMed databases. This review also involved searching on websites of international and national … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
(28 reference statements)
0
2
0
2
Order By: Relevance
“…Um fator de risco importante para maior mortalidade observado na pesquisa foi Diabetes Mellitus (DM) diagnosticado previamente, o qual teve uma correlação com o número de óbitos, representando 70% deste grupo. Essa correlação pode ser justificada devido às alterações metabólicas e vasculares, que ocorrem em pacientes com DM, responsáveis por enfraquecerem as defesas do organismo e consequentemente não responder adequadamente a infecções virais e bacterianas, como também estão associados complicações micro e macrovasculares que podem afetar a sobrevida geral do paciente 26 . Uma metanálise realizada por Guo et al comprovou que pacientes com DM prévio estão mais susceptíveis a desenvolverem infecções graves e consequentemente evoluírem com piores desfechos 27 .…”
Section: Discussionunclassified
“…Um fator de risco importante para maior mortalidade observado na pesquisa foi Diabetes Mellitus (DM) diagnosticado previamente, o qual teve uma correlação com o número de óbitos, representando 70% deste grupo. Essa correlação pode ser justificada devido às alterações metabólicas e vasculares, que ocorrem em pacientes com DM, responsáveis por enfraquecerem as defesas do organismo e consequentemente não responder adequadamente a infecções virais e bacterianas, como também estão associados complicações micro e macrovasculares que podem afetar a sobrevida geral do paciente 26 . Uma metanálise realizada por Guo et al comprovou que pacientes com DM prévio estão mais susceptíveis a desenvolverem infecções graves e consequentemente evoluírem com piores desfechos 27 .…”
Section: Discussionunclassified
“…16 This was probably related to the lower contribution to morbidity and mortality and ease of management of thyroid disorders as compared to diabetes in patients with Covid-19. [6][7][8][9] In addition, almost 40% of the research was conducted in two high-income countries, i.e., the USA and Italy. Although several low-and middle-income countries such as Brazil, Libya, and African countries have reported a high prevalence of thyroid disorders in the immediate pre-Covid era, only China and India could manage to contribute significantly to thyroid research concerning Covid-19.…”
Section: Discussionmentioning
confidence: 99%
“…While diabetes remains the most common association, other endocrine dysfunction such as adrenal insufficiency, low T3 and low TSH syndrome, hyperprolactinemia, and hypopituitarism also occur in a significant proportion of patients with moderate or severe Covid-19. [6][7][8] A recent hospital-based study found thyroid dysfunction in almost one-fourth of Covid-19 patients who underwent hormonal profiles. 7 Indeed, virtually all kinds of non-neoplastic thyroid diseases such as Hashimoto's thyroiditis, Graves' disease, subacute thyroiditis, Low T3 and low T4 syndrome, etc., have been reported to complicate Covid-19.…”
Section: Introductionmentioning
confidence: 99%
“…Esta inflamação pode levar à falência de múltiplos órgãos. A interação entre essa comorbidade e a COVID-19 pode agravar o DM preexistente ou predispor o aparecimento desta em indivíduos não diabéticos(BONANSEA et al, 2021).…”
unclassified